2022
DOI: 10.3390/polym14214729
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Poly(ethylene Glycol) Methyl Ether Methacrylates on the Selected Physicochemical Properties of Thermally Sensitive Polymeric Particles for Controlled Drug Delivery

Abstract: Thermosensitive copolymers P1–P5 of N-isopropylacrylamide (NIPA) and poly(ethylene glycol) methyl ether methacrylates (PEGMEMs) were synthesized via surfactant-free precipitation polymerization (SFPP) using ammonium persulfate (APS) at 70 °C. The polymerization course was evaluated by the conductivity. The hydrodynamic diameters and the polydispersity indexes (PDI) of P1–P5 in the 18–45 °C range, which were assessed via dynamic light scattering (DLS), were at 18° (nm): 26.07 ± 0.54 (PDI 0.65 ± 0.03), 68.00 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
(107 reference statements)
2
3
0
Order By: Relevance
“…28,30 Additionally, the appearance of distinct peaks at 0.88 ppm (a) and 1. 31,32 This confirmed that all steps of synthesis were done successfully. Also, the ratio of PEGMA to cellulose was determined by using the integral calculation under the peak of about 1.2 ppm for poly-(PEGMA) and about 4 ppm for cellulose.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…28,30 Additionally, the appearance of distinct peaks at 0.88 ppm (a) and 1. 31,32 This confirmed that all steps of synthesis were done successfully. Also, the ratio of PEGMA to cellulose was determined by using the integral calculation under the peak of about 1.2 ppm for poly-(PEGMA) and about 4 ppm for cellulose.…”
Section: Resultssupporting
confidence: 65%
“…The comparison of signal intensities in the 1 H NMR spectra provides further evidence for the formation of ester bonds between cellulose –OH groups and DDMAT carboxyl (–COOH) groups. The results showed after polymerization by PEGMA, the poly­(PEGMA) peaks at (a) 1.2 ppm, (b) 1.8 ppm, (c) 3.4–3.5 ppm, and (d) 3.3 ppm. , This confirmed that all steps of synthesis were done successfully. Also, the ratio of PEGMA to cellulose was determined by using the integral calculation under the peak of about 1.2 ppm for poly­(PEGMA) and about 4 ppm for cellulose.…”
Section: Resultssupporting
confidence: 57%
“…To obtain temperature-insensitive nonpolar suspensions, it is necessary to simultaneously prevent high-temperature-induced desorption and low-temperature-induced ordered conformation of the modifiers. In addition to introducing branched polyesters and unsaturated stearic acid to the modifiers, flexible ethylene oxide (EO) chains have the potential to disrupt the ordered conformation of a modifier at low temperatures, , which can reduce the low-temperature sensitivity of the resulting nonpolar suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor‐targeted theranostics. [ 23–35 ] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells. Many studies have shown that Zinc oxide nanoparticles can be used to provide chemotherapy agents as a cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor-targeted theranostics. [23][24][25][26][27][28][29][30][31][32][33][34][35] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells.…”
mentioning
confidence: 99%